Insight to key diazotrophic community during composting of dairy manure with biochar and its role in nitrogen transformation. (15th March 2020) - Wu, Xiaotong; Sun, Yu; Deng, Liting; Meng, Qingxin; Jiang, Xin; Bello, Ayodeji; Sheng, Siyuan; Han, Yue; Zhu, Haifeng; Xu, Xiuhong
Highlights: Biochar enhanced correlation between physicochemical factors and diazotroph community. Key diazotroph genera influencing nitrogen transformation was altered by biochar. Interaction between key diazotroph genera can influenced nitrogen transformation. Abstract: Analyzing diazotrophic community may help to understand nitrogen transformation in composting and improves the final compost quality. In this study, diazotrophic community dynamics were investigated in terms of nifH gene during dairy manure and corn straw composting with biochar addition using high-throughput sequencing. Biochar decreased the diversity of diazotrophic community and altered diazotroph community structure during composting. At phylum level, Proteobacteria, Actinobacteria and Firmicutes were dominant diazotrophic communities throughout composting process. Biochar addition registered higher correlation coefficient (R) between physicochemical factors (temperature, ammonium (NH4 + -N) and nitrate (NO3 − -N)) and diazotroph community composition. Rhodopseudomonas and Pseudoxanthomonas was the key diazotrophic communities influencing NH4 + -N transformation in control (CK) and biochar compost (BC), respectively, while for NO3 − -N transformation Clostridium and Bradyrhizobium in CK, Azospira and Methylocystis in BC served as predominant factors. These results indicated that addition of biochar altered the key diazotroph communities influencing nitrogen transformation. Furthermore, some diazotrophs (e.g. Rhodopseudomonas, Bradyrhizobium and Azospira ) affecting NH4 + -N and NO3 − -N transformation were also observed to be mediating total nitrogen (TN). Interestingly, interactions between diazotrophic communities were observed and these interactions could also influence nitrogen transformation.